Tumbuhan Indonesia Potensial Sebagai Insektisida Nabati Untuk Mengendalikan Hama Kumbang Bubuk Jagung ( Sitophilus Spp.) - Saenong, M. Sudjak (Jurnal Penelitian dan Pengembangan Pertanian, 2016)
ABSTRACTIndonesia has an abundant flora diversity. More than 400 thousand species of plants have been identified having chemical compounds and 10 thousand species of them contain secondary metabolites that are potential as a raw material of biopesticide.  The results of the study indicated that secondary metabolite compounds were able to control insect pest population. The nature and mode of action of bio-material in protecting the plants can be as antiphytopathogenic compounds (antibiotics), phytotoxic compoundsor plant growth regulator (phythotoxins, hormones and the like), and active compounds against insects (the hormone of insects, pheromones, antifeedant, repellent, attractant and insecticide). This paper discusses the use of plant-based insecticides for controlling maize weevil (Sitophilus spp.) on corn during storage. In addition to corn, this pest also damages other important food crops such as rice, sorghum and wheat. To overcome this pest, bio-insecticide could be an option. The results showed that secondary metabolites could suppress the development of pest insect populations. The secondary metabolites  in crops include volatile compounds such as essential oils, citral, geraniols, tannins, piperines, acetogenins, azadirachtin, saponin, asarone, akoragermakron, akolamonin, isoakolamin, kalameon, kalamediol, alfamirin, kaemfasterol, salannine, nimbin, nimbidin, acetogenin, and some acidic groups such as cyanide, oleanollel acid and galoyonat acid. Alkaloid almost undetectable in all the tested plants, in addition to other flavonoids that have a direct impact on the lives of insect pests.Keywords: Plants, botanical insecticide, Sitophilus spp., cornAbstrakIndonesia mempunyai keragaman flora yang sangat besar. Lebih dari 400 ribu jenis tumbuhan telah teridentifikasi bahan kimianya dan 10 ribu di antaranya mengandung metabolit sekunder yang potensial sebagai bahan baku pestisida nabati. Hasil-hasil penelitian menunjukkan senyawa metabolit sekunder dapat mengendalikan populasi serangga hama. Sifat dan mekanisme kerja bahan nabati tersebut dalam melindungi tanaman dapat sebagai antifitopatogenik (antibiotik pertanian), fitotoksik atau mengatur pertumbuhan tanaman (fitotoksin, hormon, dan sejenisnya), dan bahan aktif terhadap serangga (hormon serangga, feromon, antifidan, repelen, atraktan, dan insektisida). Tulisan ini membahas pemanfaatan insektisida nabati dalam pengendalian hama kumbang bubuk (Sitophilus spp.) pada jagung selama penyimpanan. Selain pada jagung, hama ini juga merusak komoditas tanaman pangan penting lainnya seperti padi, sorgum, dan gandum. Untuk mengatasi hama tersebut, pemanfaatan insektisida nabati dapat menjadi salah satu pilihan. Hasil penelitian menunjukkan bahwa kandungan metabolit sekunder dapat menekan perkembangan populasi serangga hama. Kandungan metabolit sekunder pada tanaman antara lain adalah senyawa atsiri seperti minyak atsiri, sitral, geraniol, tanin, piperin, asetogenin, azadirahtin, saponin, asaron, akoragermakron, akolamonin, isoakolamin, kalameon, kalamediol, alfamirin, kaemfasterol, salanin, nimbin, nimbidin, asetogenin, dan beberapa kelompok asam seperti asam sianida, asam oleanolat, dan asam galoyonat. Komponen alkaloid hampir terdapat dalam semua tanaman yang diuji, selain flavonoid lainnya yang berdampak langsung terhadap kehidupan serangga hama.